Children, youth and development - Ansell, Nicola (Routledge/Taylor & Francis Group, 2005)
Children and youth constitute a large part of the population with nearly half of the world's population under the age of twenty-five. Almost ninety percent of these people live in Third World countries. Children and youth in the Third World are affected by extremely diverse experiences, including global processes, such as development, globalization and the effects of international agreements and policies relating to children and youth. Children, Youth and Developmentfocuses on the way in which changes in development theory and practice have impacted on young people's lives and considers the influence of the differing geographical and social context in which young people live. This text addresses issues that preoccupy children and young people, or dominate policies towards them, with topics as diverse as education, child labor, street children, child soldiers, refugees, child slaves, the impact of environmental change and hazards on children and the way that children, with the enthusiasm andenergy to bring about change, can be enabled to participate in 'development.' Finally the book examines how young people are bearers of rights. This accessible textbook contains numerous student-friendly features, including boxed case studies from across the Third World, summaries of key ideas, discussion questions and annotated guides to further resources on each chapter's main topics, as well as diagrams and tables, and numerous maps and photographs.